2019
DOI: 10.1136/bmjopen-2018-025655
|View full text |Cite
|
Sign up to set email alerts
|

Importance of personal and professional experience for hospital staff in person-centred dementia care: a cross-sectional interview study using freelisting in a UK hospital ward

Abstract: ObjectiveTo detail how hospital staff with differing personal and professional caregiving experiences approach the care of patients with dementia, in order to make practical recommendations for practice.DesignCross-sectional qualitative interviews.SettingA UK hospital ward providing dementia care.ParticipantsA complete hospital ward staff team, constituting 47 hospital staff from 10 professions.MethodsHospital staff were asked to list their approaches to emotion-focused care in individual, ethnographic freelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They argue that this will be beneficial due to the exchange of knowledge and experience and stress that that this can facilitate discussions and interdisciplinary reflections about dementia-friendly routines. 55 Our integrated results suggest that the interdisciplinary focus in the dementia education intervention facilitated an improved awareness of the person with dementia. The ability to approach and see the person behind the dementia diagnosis was exemplified as being more empathic in that it aimed at accessing and recognizing the patient's emotional attitude based on the common foundation of increased outcome scores.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…They argue that this will be beneficial due to the exchange of knowledge and experience and stress that that this can facilitate discussions and interdisciplinary reflections about dementia-friendly routines. 55 Our integrated results suggest that the interdisciplinary focus in the dementia education intervention facilitated an improved awareness of the person with dementia. The ability to approach and see the person behind the dementia diagnosis was exemplified as being more empathic in that it aimed at accessing and recognizing the patient's emotional attitude based on the common foundation of increased outcome scores.…”
Section: Discussionmentioning
confidence: 75%
“…This commitment to participate in interdisciplinary cooperation was regarded as a unique result of the education intervention as it assisted the setting aside of professional boundaries and replaced it with a culture of helping, guiding, and reminding each other across occupations and seniority. This additional element of commitment of dementia education interventions in hospital settings is also stressed by Petty et al., 55 who found that dementia care and treatment in hospitals requires the incorporation of different levels of seniority and a variety of professions in dementia education planning. They argue that this will be beneficial due to the exchange of knowledge and experience and stress that that this can facilitate discussions and interdisciplinary reflections about dementia-friendly routines.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These can be shared through computerised systems and made easily accessible (Griffiths et al, 2014). As another example, expertise of staff members, including expertise of multidisciplinary colleagues and knowledge that staff have developed through building personal relationships with people with dementia, can be shared through experiential learning (Griffiths et al, 2014, Handley et al, 2017, Petty et al, 2019. Teambased learning where staff members share good practice, reflect and turn to each other for support when needed, have been recommended for nursing practice (Bridges et al, 2017).…”
Section: Discussionmentioning
confidence: 99%